marlia Administrasi Kurikulum - Lia, Mar (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2024)
Curriculum is a crucial component in a structured and tiered education system. Changes and improvements to the curriculum are needed to meet the demands of society and the development of science and technology. This article discusses the importance of curriculum administration, including planning, implementation, and evaluation, which aims to ensure the effectiveness of the teaching and learning process. In this context, the role of the teacher is very central, both as an implementer, adapter, developer, and researcher, which contributes to the success of teaching. In addition, curriculum administration also demands cooperation between all education stakeholders, including school principals and the community, to create relevant and optimal learning experiences. Through a literature review approach, this article explores the meaning, scope and functions of curriculum administration and emphasizes the importance of continuous evaluation for curriculum improvement. With good management, it is expected that education can run more effectively, efficiently and be able to produce graduates who are ready to face future challenges.